Relative secular variations of the Earth’s magnetic field in the years 1966–2016 along the profile across the main tectonic units of Poland (Zgorzelec-Wiżajny profile) - Wojas, Anna; Grabowska, Teresa (Geology, Geophysics and Environment, 2019)
The paper summarizes 50 years of research on relative local secular variations of the total magnetic intensity (TMI) along Zgorzelec-Wiżajny profile (Z-W profile) through the years 1966–2016. The Z-W profile (approximately 650 km length) cuts through Europe’s major tectonic units, including a zone of Variscan folds in the Paleozoic platform (PP), the Trans-European Suture Zone (TESZ) and the Polish part of the East European Craton (EEC). Measurements of TMI were made at 31 sites of the profile and reduced to the base recordings at the Central Geophysical Observatory in Belsk. Based on linear approximations of relative geomagnetic field values changes in time, relative annual changes in time (relative secular variations) expressed in nanoteslas [nT] per year were calculated.The study on relative geomagnetic field values revealed slower secular variations of the geomagnetic field in EEC as compared to those in PP and TESZ. However, they show lower amplitudes of these variations. An interesting phenomenon are rapid changes in the time of the relative values (trends) of TMI starting from the year 2000, also expressed as the relative secular variations per year, particularly visible in PP area. In the qualitative sense, relative secular variations show a correlation with the main geological units in the Polish territory and also important elements in the seismic and geothermal model of the lithosphere.